2008
DOI: 10.1038/eye.2008.300
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional and sub-Tenon's infusion of corticosteroids for treatment of refractory periorbital and orbital capillary haemangioma

Abstract: Purpose To evaluate the effect of combined intralesional and sub-Tenon's administration of corticosteroids for the treatment of refractory periocular and orbital capillary haemangioma in a retrospective, noncomparative study. Methods Seven infants with resistant periorbital and orbital capillary haemangioma who attended our tertiary centre from 2000 to 2005 were treated with an intralesional injection of a mixture of betamethasone 6 mg/cc and triamcinolone 10 mg/cc, by body weight, together with sub-Tenon's in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Injection can be used most easily with anterior lesions or after biopsy or partial excision of deeper orbital tumors. There have also been descriptions of techniques involving sub-Tenons injection along with injection of the hemangioma, with satisfactory results 21. For intralesional injection, Kushner recommends 40 mg of triamcinolone acetate and 6 mg preparation of betamethasone acetate and betamethasone phosphate, with a total injection volume of 1-2 ml.…”
Section: Therapymentioning
confidence: 99%
“…Injection can be used most easily with anterior lesions or after biopsy or partial excision of deeper orbital tumors. There have also been descriptions of techniques involving sub-Tenons injection along with injection of the hemangioma, with satisfactory results 21. For intralesional injection, Kushner recommends 40 mg of triamcinolone acetate and 6 mg preparation of betamethasone acetate and betamethasone phosphate, with a total injection volume of 1-2 ml.…”
Section: Therapymentioning
confidence: 99%
“…16,17 First-line therapy with corticosteroids: systemic (oral and intravenous), through local intralesional injection, periorbital infusion, or combined intralesional and posterior sub-Tenon's infusion yielded anatomical and refractive improvement. [18][19][20] However, prolonged treatment with several sessions sometimes required general anaesthesia for proper administration, and posed a risk of serious ocular and systemic side effects. 21 In cases of steroid-resistant lesions, second-line therapy with interferon-á and vincristine had an almost 100% success rate, but adverse reactions ranged from minor to very severe.…”
Section: Introductionmentioning
confidence: 99%
“…All included studies were case series, among which 15 involved propranolol therapy and 16 used corticosteroids. Twenty‐six studies examined response rates, 12 reported rebound growth rates, 13 analysed spherical power, 14 studies surveyed cylinder power, 16 looked at amblyopia rates after treatment and 21 reported adverse events . Because all of the included studies were observational studies, the MINORS score was applied to define the quality of evidence.…”
Section: Resultsmentioning
confidence: 99%
“…In the steroid groups, the most common treatment was intralesional injection of a combination of triamcinolone (40 mg) and betamethasone/dexamethasone (46 mg) . A second or third injection was necessary when the size of the lesion was insufficiently reduced.…”
Section: Resultsmentioning
confidence: 99%